Do reduced child care prices make parents work more? - Daniela Lundin; Eva Mörk; Björn Öckert (Institute for Labour Market Policy Evaluation (IFAU), 2007)
This paper exploits exogenous variation in the price of child care stemming from a major child care price reform, to estimate the effects of child care costs on parents' labour supply. The reform introduced a cap on the price that local governments could charge parents, and lead to considerable reductions in the price of child care depending on family type and region. Since the price is de-termined by a handful of observed characteristics, we are able to match house-holds that are similar in all relevant aspects, but experienced quite different price changes due to the reform. Our difference-in-differences regression matching estimates are very precise, but mostly close to zero.
Keywords: J13; J21; 330; Labour supply; price of child care; difference-in-differences regression matching; Arbeitsangebot; Kinderbetreuung; Schätzung; Schweden